Evaluation of thermal properties of thin films by IR radiometry using a comprehensive set of Zr-O-N thin films - Silva-Oliveira, C.I. da (2019)
Modulated Infrared Radiometry is a photothermal technique which allows thermal characterization of coatings. Thermal properties are determined by applying the “Extremum Method”. Zr-O-N films were deposited by sputtering to evaluate their thermal properties and the sensitivity of the method and its suitability for different film+substrate systems. Three factors were varied: i) composition/bonding: metallic Zr, crystalline metallic-type Zr-O-N and disordered ceramic Zr-O-N. The films were deposited in the metallic, reactive and poisoned regimes of the hysteresis curve; ii) each film was deposited simultaneously on three different substrates: high-speed steel, glass and silicon; iii) in each deposition batch, films with four different thicknesses were grown. Each film was deposited in the same batch with different thicknesses on top of different substrates. All of the parameters for which the model is sensitive to are explored in this matrix of 36 different samples. The thermal parameters of the films were calculated and the trends and values were examined. The trends were explained in terms of the microstructural/chemical characteristics of the films, and the influence of each substrate, depending on the film thickness. The obtained values agree with those found in literature, reflecting the nature of the films.